Beginning Oracle WebCenter Portal 12c : build next-generation enterprise portals with Oracle WebCenter Portal /: build next-generation enterprise portals with Oracle WebCenter Portal. ([2017]) - Kumar, Vinay, 1966-; García, Daniel Merchán
No abstract available